1999
DOI: 10.1046/j.1432-1327.1999.00818.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential characteristics of human 15‐lipoxygenase isozymes and a novel splice variant of 15S‐lipoxygenase

Abstract: The lipoxygenases (LOs) are a family of nonheme iron dioxygenases that catalyse the insertion of molecular oxygen into polyunsaturated fatty acids. Five members of this gene family have been described in man, 5-LO, 12S-LO, 12R-LO, 15-LO and 15S-LO. Using partially purified recombinant 15S-LO enzyme and cells constitutively expressing this protein, we have compared the activity, substrate specificity, kinetic characteristics and regulation of this enzyme to that previously reported for 15-LO. 15S-LO has a three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
64
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(73 citation statements)
references
References 51 publications
9
64
0
Order By: Relevance
“…The kinetic parameters determined for each enzyme with arachidonic acid were in agreement with values reported in the literature [2,[35][36][37]. Notably pl12-LO exhibited very similar kinetic parameters for the lipaomino acids and arachidonate.…”
Section: Kinetics Of Lipoamino Acid Oxygenation By Lossupporting
confidence: 87%
“…The kinetic parameters determined for each enzyme with arachidonic acid were in agreement with values reported in the literature [2,[35][36][37]. Notably pl12-LO exhibited very similar kinetic parameters for the lipaomino acids and arachidonate.…”
Section: Kinetics Of Lipoamino Acid Oxygenation By Lossupporting
confidence: 87%
“…Cells were processed for 15-LOX2 staining 5 weeks after infection. Representative images from one clone each of Kilty et al, 1999) or completely lack (e.g., 15-LOX2sv-b and 15-LOX2sv-c;Bhatia et al, 2003), the AA-metabolizing activity and do not produce appreciable amounts of 15(S)-HETE. Fourth, just as 15-LOX2sv-b possesses tumor-inhibitory effects (Bhatia et al, 2003), enforced expression of 15-LOX2sv-b in young NHP or PCa cells also induces cell-cycle arrest and a senescence-like phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we observed that primary NHP cells that expressed 15-LOX2, a molecule with a limited tissue distribution (i.e., prostate, lung, hair root, and cornea) and most abundantly expressed in adult prostate (Brash et al, 1997;Kilty et al, 1999), were generally big, flat, and cell-cycle arrested (Tang et al, 2002), raising the possibility that the 15-LOX2 may be associated with the NHP cell senescence. To test this possibility, we carried out triple staining for 15-LOX2, SA-bgal, and BrdU.…”
Section: Cell-autonomous Upregulation Of 15-lox2 Accompanies Nhp Cellmentioning
confidence: 99%
See 1 more Smart Citation
“…Introduction 15-Lipoxygenase 2 (15-LOX2) shows the highest homology to murine 8-LOX, has at least three splice variants (termed 15-LOX2sv-a/b/c (15-LOX2 splice variant a, b or c)), mainly metabolizes arachidonic acid (AA) to 15(S)-hydroxyeicosatetraenoic acid [15(S)-HETE], and is primarily expressed in prostate, lung, skin, and cornea (Brash et al, 1997;Kilty et al, 1999;Tang et al, 2002). 15-LOX2 expression and activity are decreased in highgrade prostate intraepithelial neoplasia and prostate cancer (PCa) (Shappell et al, 1999).…”
mentioning
confidence: 99%